Towards a framework for a new research ecosystem - Roberto Savona; Cristina Maria Alberini; Lucia Alessi; Iacopo Baussano; Petros Dellaportas; Ranieri Guerra; Sean Khozin; Andrea Modena; Sergio Pecorelli; Guido Rasi; Paolo Daniele Siviero; Roger M. Stein (European Commission, 2024)
A major gap exists between the conceptual suggestion of how much a nation should invest in science, innovation, and technology, and the practical implementation of what is done. We identify 4 critical challenges that must be address in order to develop an environment conducive to collaboration across organizations and governments, while also preserving commercial rewards for investors and innovators, in order to move towards a new Research Ecosystem.
Keywords: O3; 330; research ecosystem; Covid 19